Cord Blood Units with Low CD34+ Cell Viability Have a Low Probability of Engraftment After Double Unit Transplantation - Scaradavou, Andromachi (Biol Blood Marrow Transplant, 2009)
Double unit cord blood (CB) transplantation (CBT) appears to augment engraftment despite only one unit engrafting in most patients. We hypothesized that superior unit quality, as measured by a higher percentage of viable cells post-thaw, would determine the engrafting unit. Therefore, we prospectively analyzed 46 double unit transplants post-thaw using flow cytometry with modified gating that included all dead cells. Using a 75% threshold (mean viability minus 2SD), 20% of units had low CD34+ cell viability, with viability varying according to the bank of origin. Further, in the 44 patients with single unit engraftment, CD34+ cell viability was higher in engrafting units (p=0.0016). While either unit engrafted if both had high CD34+ viability, units with <75% viability were very unlikely to engraft: in 16 patients that received one high and one low CD34+ viability unit, only 1/16 units with viability <75% engrafted (p=0.0006). Further, in the single patient without engraftment of either unit, both had CD34+ viability <75%. Finally, poor CD34+ viability correlated with lower CFUs (p=0.02). Our data suggests one mechanism by which double unit CBT can improve engraftment is by increasing the probability of transplanting at least one unit with adequate viability and the potential to engraft.